Chaos to Order: Role of Toxin Producing Phytoplankton in Aquatic Systems - Upadhyay, R. K.; Chattopadhyay, J. (Nonlinear Analysis: Modelling and Control, 2005)
Toxin producing phytoplankton (TPP) plays an important role in aquatic systems. To observe the role of TPP, we consider a three species food chain model consisting of TPP-zooplankton-fish population. The similar type of model considered by Upadhyay et al. [1] for terrestrial ecosystem and obtained chaotic dynamics in some region of parametric space. We modify their models by taking into account the toxin liberation process of TPP population and represented as aquatic systems. We consider Holling type I, type II and type III functional forms for this process. We observe that increasing the strength of toxic substance change the state from chaos to order. Our conclusion is that TPP has a stabilizing contribution in aquatic systems and may be used as a bio-control mechanism.